An integrated process for the valorization of corn stover promoted by NaCl in a GVL/H2O system. Issue 4 (27th January 2022) - Luo, Yiping; Zhao, Zhichen; Jiang, Bin; Wei, Min; Zhang, Zheng; Zeng, Lisha; Clark, James H.; Fan, Jiajun
Abstract : An integrated green process for the valorization of corn stover with multiple functional NaCl in GVL/H2 O. Abstract : An integrated green process for the valorization of corn stover promoted by NaCl in GVL/H2 O was developed. With the addition of NaCl in 25% GVL/H2 O at 170 °C for 2 h, the interactions of NaCl (Na + and Cl − ) with the –OH group in hemicellulose and G units in lignin were enhanced, which facilitated a high extraction of hemicellulose (96.4 wt%) and lignin (86.6 wt%), obtaining cellulose-rich solid residues. NaCl promoted the extracted hemicellulose degradation to produce small molecular products (85.6%). NaCl also promoted the cleavage of β-O-4′ linkages and the decarboxylation reaction in lignin to obtain lower M w (438 Da) oligomers and monophenols (14.2%) with high selectivity of 81.9% to 4-vinylphenol, 4-vinyl guaiacol and isoeugenol. Due to the salt effects of NaCl, most of the liquid products derived from hemicellulose and lignin were in situ separated by dissolving into the aqueous and GVL phases, respectively, which provided a possibility for further utilization. In addition, the obtained cellulose-rich solid residues were activated by steam to prepare high performance activated carbon ( S BET = 819 m 2 g −1, A methylene blue = 212 mg g −1 and A iodine = 914 mg g −1 ), which showed great potential for pollution control within many industrial processes. This opened an avenue to integrate the valorization of corn stover.